1981
DOI: 10.1007/bf00256681
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of prolactin and testosterone in the human prostate

Abstract: Three experiments were performed to determine whether human prolactin (hPr) affects prostatic uptake and metabolism of testosterone (T). 1) Patients with prostatic cancer were infused twice with radio-labelled androgens, the first time with basal hPR, the second time with oral thyrotrophin-releasing hormone (TRH)-elevated hPr. In 5/7, significant increases in metabolic clearance of dihydrotestosterone (DHT) and in conversion of T to DHT accompanied increased hPR. 2) The incorporation of labelled T into minced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…PRL has emerged as the pituitary hormone most likely to account for prostate gland evolution [35], The proliferative effects of PRL are closely associated with androgens. Indeed, PRL can act indirectly on the prostate by altering androgen biosynthe sis at the testis [ 14], or directly in synergism with testoster one by an 'increase in androgen nuclear receptors' [10].…”
Section: Discussionmentioning
confidence: 99%
“…PRL has emerged as the pituitary hormone most likely to account for prostate gland evolution [35], The proliferative effects of PRL are closely associated with androgens. Indeed, PRL can act indirectly on the prostate by altering androgen biosynthe sis at the testis [ 14], or directly in synergism with testoster one by an 'increase in androgen nuclear receptors' [10].…”
Section: Discussionmentioning
confidence: 99%
“…Farnsworth, Slaunwhite, Sharma, Oseko, Brown, Gonder & Cartagena (1981) have shown that the uptake of radiolabelled testosterone by benign prostatic hyperplasia (BPH) was markedly increased by the addition of the prolactin but the existence of specific prolactin-binding sites is controversial (Keenan, Kemp, Ramsey, Garrison, Pearse & Hodges, 1979;Blankenstein, Bolt-De Vries & Schröder, 1982). Recent investigations using an immunocytochemical staining technique have, however, indicated the presence of a prolactin-like molecule in the human prostate gland (Harper, Sibley, Peeling & Griffiths, 1981).…”
Section: Introductionmentioning
confidence: 97%
“…Prolactin has been implicated in the pathogenesis of prostate cancer [18][19][20][21][22], but there is no evidence suggesting a direct effect of PRL on prostate cancer cells in vivo. Bartsch et al [23,24] observed higher than normal PRL levels in 15-20% of subjects with prostatic cancer.…”
Section: Introductionmentioning
confidence: 99%